Effects of interruptions of controlled‐rate freezing on the viability of umbilical cord blood stem cells. Issue 1 (14th July 2014) - Yang, Hongyou; Pidgorna, Alla; Loutfy, Mona R.; Shuen, Paul
<x xml:space="preserve">Abstract</x> Background An optimal cooling rate is critical for cryopreserving cord blood stem cells, so it is generally achieved by using controlled‐rate freezers (CRFs). The cooling rate can be interrupted by many factors during cooling; therefore, a proper response to the interruption in cryopreservation is crucial to prevent the loss of valuable cells. Study Design and Methods Cord blood samples (n = 6) containing 10% dimethyl sulfoxide were cooled from 4 to −80°C using a CRF. At different temperatures during cooling, cells were transferred either to liquid nitrogen vapor phase (LNVP) directly or a −80°C mechanical freezer where they were stored for 18.1 ± 0.6 hours before transferring to LNVP. The cells were stored in LNVP for 127 ± 48.1 hours before postthaw recovery, viability, and survival of total nucleated cells and/or CD45+ cells, CD34+ cells, and colony‐forming unit–granulocyte‐macrophage (CFU‐GM) were assessed. Results For all types of postthaw evaluations, there were no significant differences when cells were transferred to a −80°C freezer before LNVP, regardless of the temperature at which cooling was interrupted. In contrast, there were significant differences when cells were transferred to LNVP directly, but the differences were determined by the type of assays and how viability was calculated. Conclusions Cord blood samples can be transferred to a −80°C freezer anytime during controlled‐rate cooling, but should only be transferred to LNVP when the samples have been cooled to −40°C or lower. Percent postthaw survival of CFU‐GM should be routinely assessed when controlled‐rate cooling is interrupted.